2005
DOI: 10.4049/jimmunol.175.7.4392
|View full text |Cite
|
Sign up to set email alerts
|

Signal 3 Tolerant CD8 T Cells Degranulate in Response to Antigen but Lack Granzyme B to Mediate Cytolysis

Abstract: Naive CD8 T cells that respond in vivo to Ag and costimulation in the absence of a third signal, such as IL-12, fail to develop cytolytic function and become tolerized. We show in this study that CD8 T cells purified from TCR transgenic mice and stimulated in vitro in the presence or absence of IL-12 form conjugates with specific target cells, increase intracellular Ca2+, and undergo degranulation to comparable extents. Perforin is also expressed at comparable levels in the absence or presence of a third signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 41 publications
(48 reference statements)
4
57
0
Order By: Relevance
“…2B). These results suggested that the CD107a-based degranulation assay may not precisely identify effector CD8 T cells involved in cytolysis, a finding that had been reported previously (18). Next, we questioned whether low cytotoxic activity despite normal degranulation could be explained by changes in expression level of grB, or perhaps perforin, in the cytotoxic granules of briefly stimulated OT-I cells.…”
Section: Briefly Stimulated Cd8 T Cells Show Deficiency In Cytotoxicitymentioning
confidence: 45%
“…2B). These results suggested that the CD107a-based degranulation assay may not precisely identify effector CD8 T cells involved in cytolysis, a finding that had been reported previously (18). Next, we questioned whether low cytotoxic activity despite normal degranulation could be explained by changes in expression level of grB, or perhaps perforin, in the cytotoxic granules of briefly stimulated OT-I cells.…”
Section: Briefly Stimulated Cd8 T Cells Show Deficiency In Cytotoxicitymentioning
confidence: 45%
“…Absence of lytic function may suggest partial tolerance (41). However, at least in mice, some nonlytic CD8 T cells have protective potential, for example, by IFN-␥ secretion important for CD8 T cell-mediated tumor defense (49) and protection against some viruses (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Perforin molecules punch holes into the membrane of the target cell and GzB penetrates inducing apoptosis via activation of caspase pathways [21][22][23]. While resting CD8 + cells (naïve and central memory cells) have no cytolytic granules containing GzB, they start expressing granzyme within days after antigen encounter -provided they also receive "signal 3" [12,23]. In the absence of ongoing antigen stimulation CD8 + cells stay GzB positive for approximately one month [24].…”
Section: Introductionmentioning
confidence: 99%
“…Naïve CD8 + cells will proliferate vigorously but will not differentiate in lytic effector cells unless they also receive a "third signal" that can be provided by IL-12 [9,10] or type I IFNs [11]. In the absence of such third signals, CD8 + cells will proliferate, express perforin but not Granzyme B (GzB) and will lack cytolytic functions [12]. If the immune response is successful and the antigen is cleared/controlled the CD8 + cells become quiescent, their clonal sizes drop, they reacquire a resting phenotype and lose the ability to engage in direct lytic effector functions.…”
Section: Introductionmentioning
confidence: 99%